PENDEKATAN DAKWAH DALAM KAEDAH PENGAJARAN KEPADA MUALLAF - Noraini Mohamad; Mariam Abd. Majid; Badlihisham Mohd Nasir (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2018)
Dakwah approach in the teaching method to the mualaf is a headline that deals with the application of the concept of dakwah in the teaching method to mualaf. The object of this study is to examine appropriate teaching methods to mualaf based on several dakwah approaches that exist in the al-Qur'an and al-Sunnah. The method use in this study is literature review using qualitative document analysis techniques. The study shows that there are many dakwah approaches that may be used in the teaching method to mualaf is the teaching based on the rules of al-Qur’an, the teaching based on the approach of the Rasulullah SAW and the lesson about approach. This lesson will contribute to the teachers of mualaf especially in particular and the general preachers. The implications of the study are that some of the methods found in this study may be used by teachers of mualaf especially when carrying out teaching activities. Likewise preachers, some of the findings in this study may be used while performing dakwah activities. Keywords: Dakwah Approaching, Teaching Method, Mualaf